2018
DOI: 10.1021/acs.jpcb.7b09061
|View full text |Cite
|
Sign up to set email alerts
|

Application of Classical Thermodynamics to Conductivity in Nonpolar Media: Experimental Confirmation

Abstract: We previously proposed ( Gourdin-Bertin , S. and Chassagne , C. J. Chem. Phys. 2016 , 144 ( 24) ) a simple theoretical model to account for the evolution of conductivity with dielectric permittivity in nonpolar media. In this article, we validate the theory experimentally for the case of an ionogenic species kept at a constant chemical potential (i.e., in equilibrium with a nondissolved salt, in contrast to previously published conductivity measurements carried out as a function of various fully dissolved salt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…In a subsequent investigation of toluene mixtures with several different alcohols, Dukhin and Parlia [33] suggested that electrical conductivity depends on the concentration of ion pairs, which varies with the dielectric constant of the mixtures. However, others have subsequently questioned these explanations, on the grounds that they do not adhere to classical thermodynamics [34,35]. In addition, Gourdin-Bertin and Chassagne [34] reasoned that autoprotolysis would not account for the observed electrical conductivity behavior because only very low concentrations of ionic species would be present.…”
Section: Electrical Conduction In Non-aqueous Liquidsmentioning
confidence: 99%
See 3 more Smart Citations
“…In a subsequent investigation of toluene mixtures with several different alcohols, Dukhin and Parlia [33] suggested that electrical conductivity depends on the concentration of ion pairs, which varies with the dielectric constant of the mixtures. However, others have subsequently questioned these explanations, on the grounds that they do not adhere to classical thermodynamics [34,35]. In addition, Gourdin-Bertin and Chassagne [34] reasoned that autoprotolysis would not account for the observed electrical conductivity behavior because only very low concentrations of ionic species would be present.…”
Section: Electrical Conduction In Non-aqueous Liquidsmentioning
confidence: 99%
“…Moreover, the role of composition-dependent ion pairing was also questioned [34]. However, on the whole, even though the previous studies have presented accompanying theories that apparently give acceptable fits to the experimental data, the overall picture is confusing, with impurities also being implicated, including water [34][35][36], with the overall conclusion being that further work was required [34].…”
Section: Electrical Conduction In Non-aqueous Liquidsmentioning
confidence: 99%
See 2 more Smart Citations
“…More rarely the conductivity of surfactant solutions is enhanced using mixtures of polar and nonpolar solvents. For example, it was shown in [32] that conductivity of AOT solutions in the ethanol–toluene mixtures increases from 5 × 10 −11 to 10 −4 S/m with raising the ethanol content in the mixture. It is known also that the addition of chloroform to nonpolar solvents increases conductivity of the solutions [33, 34].…”
Section: Introductionmentioning
confidence: 99%